Quality Of Health Among Methadone Maintenance Treatment (Mmt) Program Clients In Myanmar - Tun, Sun (2020)
HIV prevalence rate among PWIDs (People who inject drugs) in Myanmar is high at 28.5% based on 2014 IBBS results. More than 13,441 (16% of the estimated 83,000 PWIDs) have been on methadone treatment in 2017. Evaluation of the methadone program is vital for efficient service delivery. This study aimed to understand the context and important treatment factors of methadone maintenance treatment (MMT) program among clients in Myanmar